2020
DOI: 10.1136/bmjopen-2019-029660
|View full text |Cite
|
Sign up to set email alerts
|

LIFEStyle, Prevention and Risk of Acute PaNcreatitis (LIFESPAN): protocol of a multicentre and multinational observational case–control study

Abstract: IntroductionAcute pancreatitis (AP) is a life-threatening inflammatory disease of the exocrine pancreas which needs acute hospitalisation. Despite its importance, we have significant lack of knowledge whether the lifestyle factors elevate or decrease the risk of AP or influence the disease outcome. So far, no synthetising study has been carried out examining associations between socioeconomic factors, dietary habits, physical activity, chronic stress, sleep quality and AP. Accordingly, LIFESPAN identifies risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…[29][30][31] .A recent study was also carried out to identify risk factors of acute pancreatitis and help to prepare preventive recommendations for lifestyle elements. 32 Emerging evidence suggests that VEGF plays an important role in the host inflammatory response in many diseases. 33,34 Several studies have also confirmed that VEGF plays an effect in inflammatory response mainly by binding to Flt-1.…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31] .A recent study was also carried out to identify risk factors of acute pancreatitis and help to prepare preventive recommendations for lifestyle elements. 32 Emerging evidence suggests that VEGF plays an important role in the host inflammatory response in many diseases. 33,34 Several studies have also confirmed that VEGF plays an effect in inflammatory response mainly by binding to Flt-1.…”
Section: Discussionmentioning
confidence: 99%
“… 66 67 Socioeconomic status will be assessed at baseline and at 12 and 24 months with the questionnaire used in the LIFESPAN study. 68 …”
Section: Methodsmentioning
confidence: 99%
“…66 67 Socioeconomic status will be assessed at baseline and at 12 and 24 months with the questionnaire used in the LIFESPAN study. 68 The aetiology of each recurrent episode will be determined following current international guidelines, but all episodes will be included in the primary endpoint. 4 34 Blood pressure, heart rate and body weight will be measured by an independent nurse blind to the allocation at every visit.…”
Section: Assessmentmentioning
confidence: 99%
“…It has been reported that intake of vegetables, fish, fiber, and milk may reduce the risk of AP. [38][39][40] Results of a prospective cohort study of 0.5 million people showed that there was an inverse association between physical activity and risk of AP. 41 It has also been reported that combined aerobic exercise and resistance exercise may reduce the occurrence of sarcopenia obesity and improve muscle function.…”
Section: Dovepressmentioning
confidence: 99%